Inculturation and the Growth of the Baptist Missionary Enterprise in the Niger Delta, 1950-2005 - Onia, Misoma Michael (2015)
This study examined the factors responsible for the growth of the Baptist missionary enterprise in the Niger Delta from 1950 to 2005. It also investigated the ways Baptists had responded to the traditional worldviews and culture of the peoples of the Niger Delta with particular reference to burial customs, marriage, polygamy, widowhood and traditional rulership. The study further assessed the impact of inculturation on the doctrinal emphases, practices, and pastoral leadership of the Niger Delta Baptists. This was with a view to understanding the complex interaction between the Baptist faith and the African culture in the Niger Delta.